Short Run and Long Run Interest Rate Interrelations in India: A Granger Causality Approach - Chaudhry, Archna (Economic Journal of Nepal, 2014)
Expectations theory of term structure of interest rate is oldest and most common. On its theoretical underpinnings the present paper tries to explore the relationship of short (monthly average of call money rate) and long (ten year government securities’ month end return) run rate of interest in India. Data provides scope to test for the impact of policy or institutional changes on the expectations theory. We have studied the relationship with the help of Granger –causality approach and our results suggest that both variables are integrated of order one and a long run relation exists between them. The null hypothesis that changes in long run rate do not cause changes in the short run rate can be rejected for all time lags under review. The Economic Journal of Nepal, Vol. 34, No. 3, July-September 2011